The Influence of Education and Income Poverty in East Java - Iftitakhul Ilmi Nasibhul Janah; Ady Soejoto; Norida Canda Sakti (Technium Social Sciences Journal, 2021)
This study aims to analyze the effect of education level and income on poverty in East Java either partially or simultaneously. The population in this study are East Java Province 2014-2018. This study uses a quantitative approach. The sampling technique with purposive sampling technique. The data collection method used is a method of documentation. The education variable is indicated by senior high school graduates equivalent, income is indicated by income per capita, and the number of poor people is taken from poverty information data based on the average expenditure per capita per month. The population in this study is the percentage of education aged 15 years who completed or equivalent to senior high school, data per capita income and poverty from 38 districts / cities. The samples taken by the researcher were 2 districts / cities with a high number of poor people in each the coordination territory While the method of analysis uses techniques panel data regression analysis. Based on the test results in this study, it is found that education and income have a significant effect on poverty.